2022
DOI: 10.37641/riset.v4i2.156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interprofessional Collaboration and Transformational Leadership on Patient Safety With Work Motivation as Intervening Variables

Abstract: The purpose of this study was to obtain empirical evidence of the role of work motivation in mediating the relationship between interprofessional collaboration and transformational leadership on patient safety in inpatient installations using a cross-sectional study design. Moreover, make 250 inpatient installation nurses with civil servant status as the unit of analysis. The study's results prove that interprofessional collaboration and transformational leadership positively and significantly affect work moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Previous studies showed that transformational leadership has a significant impact on patient safety culture and the perceived level of patient safety. 37 , 54 , 55 Moreover, many studies declared that patient safety culture has a positive impact on patient safety perceptions and outcomes. 8 , 11 , 56 The current study revealed that transformational leadership and patient safety culture has also significant association with nurses’ practices related to patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that transformational leadership has a significant impact on patient safety culture and the perceived level of patient safety. 37 , 54 , 55 Moreover, many studies declared that patient safety culture has a positive impact on patient safety perceptions and outcomes. 8 , 11 , 56 The current study revealed that transformational leadership and patient safety culture has also significant association with nurses’ practices related to patient safety.…”
Section: Discussionmentioning
confidence: 99%